Laboratory manual introductory plant biology - Stern, Kingsley R. (McGraw- Hill, 2006)
This introductory text assumes little prior scientific knowledge on the part of the student. It includes sufficient information for some shorter introductory botany courses open to both majors and nonmajors, and is arranged so that certain sections can be omitted without disrupting the overall continuity of the course. Stern emphasizes current interests while presenting basic botanical principles.